Existence and Development of Islam in the Ottoman Empire Region: The Process of Establishment, Growth, and Evolution - Nuraidah, Syifa; Syahroni, Roni; Hernawan, Wawan; Kusdiana, Ading (Yayasan Mentari Madani, 2023)
This research aims to analyze the existence and development of Islam in the Ottoman Empire's territory, with a focus on its inception, growth, and evolution. The aspects under scrutiny encompass the political system, governance, state structure, intellectual progress, religious studies, and culture. This studly employs a historical approach to depict how Islam played a pivotal role in shaping and transforming the Ottoman Empire, from its inception to its zenith. In its early stages, Islam acted as a unifying force for diverse ethnic groups and tribes within the region. The political and governance systems, rooted in Islamic principles, contributed to the empire's stability and continuity. As the empire evolved, it emerged as a center of intellect and religion. Intellectual progress is reflected in the establishment of madrasas and other educational institutions that advanced knowledge and Islamic thought, fostering an environment conducive to the growth of religious studies, culture, and the arts. Nonetheless, the empire's development was marked by dynamics that influenced its state structure and political framework. The Ottoman Empire faced challenges from internal and external factors, impacting its political and economic stability. These challenges prompted changes in governance and administrative systems. In conclusion, Islam played a significant role in shaping and guiding the trajectory of the Ottoman Empire. The Islamic-based political and governance systems, coupled with intellectual development, religious studies, and cultural advancements, made substantial contributions to sustaining the empire's existence and growth. However, changes in internal and external dynamics also shaped the evolution of the state and its governance. This study provides profound insights into Islam's role in the history of this region and its repercussions on social, political, and cultural transformations